Functional status and amount of hip displacement independently affect acetabular dysplasia in cerebral palsy. (22nd April 2017) - Chung, Myung Ki; Zulkarnain, Arif; Lee, Jae Bong; Cho, Byung Chae; Chung, Chin Youb; Lee, Kyoung Min; Sung, Ki Hyuk; Park, Moon Seok
Abstract : Aim: Acetabular dysplasia is the one of main causes of hip displacement in patients with cerebral palsy (CP). Although several studies have shown a relationship between hip displacement and acetabular dysplasia, relatively few have evaluated the association between quantitative acetabular dysplasia and related factors, such as Gross Motor Function Classification System (GMFCS) level. Method: We performed a morphometric analysis of the acetabulum in patients with CP using multiplanar reformation of computed tomography data. The three directional acetabular indices (anterosuperior, superolateral, and posterosuperior) were used to evaluate acetabular dysplasia. Consequently, linear mixed‐effects models were used to adjust for related factors such as age, sex, GMFCS level, and migration percentage. Results: A total of 176 patients (mean age 9y 5mo, range 2y 4mo–19y 6mo; 104 males, 72 females) with CP and 55 typically developing individuals (mean age 13y 6mo, range 2y 5mo–19y 10mo; 37 males, 18 females) in a comparison group were enrolled in this study. Statistical modelling showed that all three directional acetabular indices independently increased with GMFCS level ( p <0.001) and migration percentage ( p <0.001). Interpretation: Acetabular dysplasia was independently affected by both the amount of hip displacement and the GMFCS level. Thus, physicians should consider not only the migration percentage but also three‐dimensional evaluation in patients at high GMFCS levels. What this paper adds: Acetabular dysplasia is independently aggravated according to increased migration percentage and Gross Motor Function Classification System level. Three‐dimensional evaluation should be considered when deciding the pelvic osteotomy in patients with cerebral palsy. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.